Maze Of Faith : Shalat yang Sempurna - Muzzammil Rahmat Edi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2024)
The development of the gaming industry demands developers to create more immersive playing experiences. In this context, the use of Finite State Machine (FSM) has become a popular and effective solution for managing storyline progression and structured character development. This article discusses the basic concepts of FSM and illustrates its implementation in the game